The Views of Teachers of Science and Art Centres about the Institution - Semerci, Nuriye; Kaya, Esin (Tokat Gaziosmanpaşa Üniversitesi, 2007)
The aim of this study is to define the views of the teachers, who for Science and Art Centres (BİLSEM). With this aim survey method was employed in this study. The study is carried out among 88 teachers employed in six Science and Art Centres. The exemplification is done through 61 teachers chosen among these teachers. The data is collected via a questionnaire which contained information related to the teacher and school, and was developed by researchers. Data was analysed in percentage and chisquare test. The results of the study indicate that the teachers have no negative thoughts about BİLSEM and no difficult job context but they want to communicate with universities and other BİLSEMs. In addition, they emphasized the importance of inservice training and pointed out the necessity of making it continual. Considering this data, it can be suggested that communication between the universities and BİLSEMs be provided and in-service training made continual.

Bu çalışmanın amacı, Bilim ve Sanat Merkezlerinde (BİLSEM) görev yapan öğretmenlerin BİLSEM’e yönelik görüşlerini belirlemektir. Bu amaçla, araştırmada tarama modeli kullanılmıştır. Araştırmanın evreni altı Bilim ve Sanat Merkezinde görev yapan 88 öğretmendir. Örneklemi ise bu öğretmenler içerisinden seçilen 61 öğretmen oluşmuştur. Veriler; araştırmacılar tarafından geliştirilen öğretmene ve okula ait bilgileri içeren anket formuyla toplanmıştır. Veriler frekans yüzde ve ki-kare ile analiz edilmiştir. Araştırmanın sonunda öğretmenlerin BİLSEM’e yönelik olumsuz görüşlerinin bulunmadığı, çalışırken zorlanmadıkları, ancak diğer BİLSEM’ler ve üniversitelerle iletişim kurmak istedikleri belirlenmiştir. Bunun yanında hizmetiçi eğitimin önemini vurgulayarak sürekli hale getirilmesinin gerekliliğinden bahsetmişlerdir. Buna dayanarak, BİLSEM’lerin bulunduğu illerdeki üniversitelerle işbirliğinin sağlanması, hizmetiçi eğitimin sürekli hale getirilmesi gibi öneriler verilebilir
Bilim ve Sanat Merkezlerinde (BİLSEM) Görev Yapan Öğretmenlerin BİLSEM’e Yönelik Görüşleri